Kesan-Kesan Pewartaan Melaka Bandaraya Bersejarah Sebagai Tapak Warisan Dunia oleh UNESCO - Omar, Nurfashihah (Research in Management of Technology and Business, 2021)
Although research on World Heritage Sites (WHS) has begun internationally since 1945, studies on the effects of the recognition of the declaration of Melaka Historic City as a World Heritage Site in Malaysia are still lacking. This study examine the implications of Melaka historic city after 12 years of inscription under UNESCO World Heritage Site. There are two main objectives of this study which firstly to identify important indicators in the recognition of WHS and secondly, to identify the impact of the inscriptions before and after Melaka Historic City has been inscribed under WHS. This study uses qualitative methods and was implemented through semi-structured interview and observation as data acquisition tools. This study has been conducted within Bandar Hilir Melaka which is the core zone and has significant historical relics and is the basis for the inscription given. The findings of the study has found that there are several important indicators that have been identified as the basis in determining the impact of the inscription as WHS. In addition, this study has identified the effects of the declaration from both positive and negative side. The inscription of Melaka Historic City as WHS has given various positive impacts, especially for tourism industry.